Kolaborasi Orangtua dan Guru: Upaya Membentuk Kembali Akhlakul Karimah Bagi Anak - Mulyana, Ida (Indonesian Journal of Teaching and Teacher Education, 2024)
Morals are very important for every person, especially for every Muslim. The formation of morals through moral education needs to be given to every child by parents since childhood. Childhood is the most important period in educating children, so there are not a few children who are educated and not educated properly by their parents. This research explains the urgency of current behavior or morals that have deviated from existing teachings. Therefore, this research aims to find how to rebuild children's moral education, both from educational patterns from parents and educational institutions. This research uses a qualitative approach method, with data derived from secondary data. Data collection techniques were carried out with documentation studies. Then, descriptive data analysis was carried out and finally conclusions were drawn. the importance of moral education for children, starting from the role of parents from an early age. Although schools and madrasahs have an important role in shaping character, collaboration with the family environment is often less than optimal. Parents are expected to remain the main pillar in shaping children's morals, although not all children get adequate moral education from their parents. Active collaboration between parents and teachers, especially in madrasah, is needed to instils the values of discipline and honesty in children. In the Islamic context, family education reinforces the importance of religious teachings in daily life. Suggestions to strengthen the role of madrasah as a formal institution that integrates Islamic religious education as a whole, increase collaboration with parents through open communication, and organize training for parents, are expected to increase the effectiveness of children's moral education holistically.